DIAGNOSTIC APPROACHES IN ONCOLOGY: FROM BIOPSY TO LIQUID BIOPSY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Advancements in oncology have revolutionized diagnostic approaches, transitioning from conventional tissue biopsies to cutting-edge liquid biopsies. These methodologies provide critical insights into tumor biology, enabling early detection, precise monitoring, and tailored therapeutic strategies. This article explores the evolution of diagnostic techniques in oncology, emphasizing modern methods such as next-generation sequencing (NGS), circulating tumor DNA (ctDNA) analysis, and the role of liquid biopsies. Furthermore, it highlights the achievements of contemporary medicine in improving patient outcomes through innovative diagnostic tools.